ANALISIS KEMAMPUAN BERPIKIR KREATIF DAN KOMUNIKASI MATEMATIK SERTA KEMANDIRIAN BELAJAR SISWA SMP MELALUI PEMBELAJARAN DISCOVERY LEARNING - Yogi Purnama; Sandra Dwi Setianingrum; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to analyze the ability of creative thinking and mathematical communication and the independence of junior high school students through Discovery Learning learning. This research method uses a qualitative descriptive method. The place of research was carried out in one of the junior high schools in West Bandung Regency. The population of this research is the eighth grade students of SMP Negeri 4 Ngamprah in the material of Relations and Functions. The research subjects were students of class VIII B. To obtain the research data, the instruments were used in the form of test questions and questionnaires for learning independence. The results of the study concluded: (1) Discovery Learning learning increases students' motivation to learn and mathematical communication; (2) the attitude of learning independence in students still needs to be improved; (3) Understanding students of the Concept needs to be improved in order to achieve more optimal results.